Hypertensive Disease of pregnancy(HDP) Gestosis Score Assessment for the Prediction of Pre-eclampsia : A Diagnostic Study - Pandey, Shuvechha; Man Singh Karki, Gyanendra; KC, Heera (Birat Journal of Health Sciences, 2024)
Introduction: Preeclampsia, marked by hypertension and proteinuria after 20 weeks of gestation, leads to severe maternal and fetal complications globally. The current diagnosis for preeclampsia includes blood pressure measurement with or without proteinuria. The HDP-Gestosis Score integrates clinical, laboratory, and imaging markers to enhance early detection and improve outcomes. There is a gap in diagnostic accuracy of HDP-Gestosis score in Nepalese context. Objective: This study aimed to evaluate the diagnostic accuracy of the HDP-Gestosis Score for predicting preeclampsia, focusing on its sensitivity, specificity, positive predictive value, and negative predictive value. Methodology: A prospective hospital-based study was conducted at Birat Medical College Teaching Hospital from 15 September 2023 to 10 July 2024. Data were collected from 284 consecutively enrolled antenatal patients and followed until delivery to predict the occurrence of preeclampsia and analysed using SPSS version 23. Results: The incidence of Preeclampsia and Gestational Hypertension was 5(1.8%) and 20( 7% ) respectively. The HDP Gestosis Score distribution with a score of 1,2 and ≥3 showed 26.04%, 29.6% and 30.28% respectively. The sensitivity and negative predictive value of the HDP Gestosis Score were both 100%, while specificity was 70.96% and positive predictive value was 5.81%. Conclusion: The HDP Gestosis Score demonstrates high sensitivity and negative predictive value in predicting preeclampsia, making it an effective tool for ruling out the condition in low-resource settings. However, its specificity was moderate, and the positive predictive value was low, suggesting use alongside other diagnostic methods.